Seepage effect on open-channel flow and incipient sediment motion - Cheng, Nian Sheng. (2009)
This study presents the experimental results and theoretical analyses on seepage effects on the structural features of open-channel flow and the critical condition for sediment entrainment. Experimental investigations were conducted in two laboratory flumes with permeable sediment boundaries. The results on the structure of open-channel flow show that an upward seepage through the sediment bed causes changes in the velocity distributions, the rms values of velocity fluctuations, the Reynolds shear stress and the shear velocity. Along the seepage zone, the streamwise velocity is increased almost through the entire water depth, but the increase is much more apparent near the free-surface than the permeable boundary. On the other hand, the rms values of velocity fluctuations increase more significantly near the bed than the surface of the flows. The velocity distribution subjected to seepage can be described by the modified logarithmic law, which was derived on the basis of the assumption of the equilibrium layer. The roughness function included in the modified logarithmic law depends not only on the roughness Reynolds number but also on the dimensionless seepage velocity.